Pengaruh CSR, GCG, Struktur Modal, Ukuran Perusahaan Terhadap Nilai Perusahaan: Studi pada Perusahaan Properties & Real Estate yang Terdaftar di BEI Periode 2022-2024 - Fitria Salva Rima; Enny Susilowati Mardjono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), capital structure, and firm size on firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach with an associative method. The sample was determined using purposive sampling, resulting in 35 companies with a total of 105 observations. The data used are secondary data obtained from annual reports and financial statements, which were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that CSR and capital structure have a positive and significant effect on firm value. Meanwhile, firm size has a negative and significant effect on firm value. GCG variables proxied by managerial ownership, institutional ownership, and independent commissioners show no significant effect, while the audit committee has a negative and significant effect on firm value. Simultaneously, all independent variables explain 39.7% of the variation in firm value. These findings suggest that not all corporate governance mechanisms effectively enhance firm value, highlighting the need to optimize GCG implementation and improve CSR quality as well as capital structure management.